Understanding individual and collective response to climate change: The role of a self-other mismatch - Harrington, Rosie; Nugier, Armelle; Khamzina, Kamilla; Guimond, Serge; Monceau, Sophie; Streith, Michel (Frontiers in Psychology, 2022)
Several scientists have shown the importance of mitigating global warming and have highlighted a need for major social change, particularly when it comes to meat consumption and collective engagement. In the present study (N = 486), we conducted a cross-sectional study to test the mismatch model, that aims at explaining what motivates individuals to participate in normative change. This model stipulates that perceiving a self – other difference in pro-environmental attitudes is the starting point and can motivate people to have high pro-environmental intentions. This mismatch effect is explained by participants willingness to participate in normative and social change: people that perceive a gap between their personal attitude and the social norm should be more willing to participate in normative change. This should then motivate them to have high pro-environmental intentions on an individual and group level. The results confirm the hypothesized model on an individual and group level and explain how people can be motivated to participate in normative change. Implications of these findings and the need for further studies are discussed.